2013
DOI: 10.1016/j.wocn.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Reassignment of consonant allophones in rapid dialect acquisition

Abstract: International audienceIn an experiment spanning a week, American English speakers imitated a Glaswegian (Scottish) English speaker. The target sounds were /t/ and /r/, as the Glaswegian speaker aspirated wordmedial /t/ but pronounced /r/ as a flap. This experiment therefore explored whether speakers could learn to reassign a sound they already produce (the flap) to a new phoneme and to new phonetic contexts. Speakers appeared to learn systematically, as they could generalize to words which they had never heard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 61 publications
(86 reference statements)
4
41
0
Order By: Relevance
“…Other studies have shown that lexical encoding and memory are compromised for dialects that are lowstatus or non-standard, even when word recognition has not been affected (Sumner & Samuel, 2009;Clopper, Tamati, & Pierrehumbert, 2016). Turning to production, German, Carlson, and Pierrehumbert (2013) describe an imitation experiment in which American English speakers learning the allophones of /t/ and /r/ of a Glaswegian English speaker generalize the target patterns to other words. They retain the ability to generalize the patterns one week later, when their knowledge of the Glaswegian dialect is re-activated by hearing speech recordings that do not contain any examples of the target patterns.…”
Section: Social-indexical Informationmentioning
confidence: 99%
“…Other studies have shown that lexical encoding and memory are compromised for dialects that are lowstatus or non-standard, even when word recognition has not been affected (Sumner & Samuel, 2009;Clopper, Tamati, & Pierrehumbert, 2016). Turning to production, German, Carlson, and Pierrehumbert (2013) describe an imitation experiment in which American English speakers learning the allophones of /t/ and /r/ of a Glaswegian English speaker generalize the target patterns to other words. They retain the ability to generalize the patterns one week later, when their knowledge of the Glaswegian dialect is re-activated by hearing speech recordings that do not contain any examples of the target patterns.…”
Section: Social-indexical Informationmentioning
confidence: 99%
“…To model the interaction of spoken word recognition and expectations derived from, in this case, visually presented social cues, it is necessary to integrate a neo-generative model of speech perception (Pierrehumbert, 2002;German et al, 2013) with an attention-weighting mechanism (Johnson, 1997) and connect this to a model of person construal (Freeman and Ambady, 2011). Under such a model, abstract phonological generalizations or categories are connected with multidimensional phonetic distributions (Pierrehumbert, 2002).…”
Section: Listeners Show a Drop In Intelligibility For Chinesementioning
confidence: 99%
“…Sub‐phonemic abstraction is compatible with the idea that non‐contrastive phonetic variants can form part of the lexicon (Kiparsky, , ) and with recent studies from perceptual learning showing that listeners adapt to units that are more fine‐grained than the phoneme (Reinisch & Mitterer, ; Reinisch, Wozny, Mitterer, & Holt, ). There is also other evidence for sub‐phonemic processing from second language (Polka, ) and new dialect learning (German, Carlson, & Pierrehumbert, ). Splitting and merging were also agent‐specific in the IP‐model.…”
Section: Discussionmentioning
confidence: 97%